Strategic Formulation of Dasatinib Nanosponges by Box–Behnken Design for an Improved Oral Delivery - Saritha Chukka (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: Dasatinib (DAS) a second-generation tyrosine kinase inhibitor has proven to be highly effective in inhibiting the growth of tumors but suffers from low solubility. Materials and Methods: The objective of this research was to create innovative nanosponges (NSPs) using hydroxypropyl-β-cyclodextrin (HPβCD) polymer for delivery of DAS a hydrophobic anticancer drug to expand its oral bioavailability using a factorial design approach as a tool for optimization methodology. Results and Discussion: Formulation and process variables were optimized for developing NSPs using Design-Expert® software. Particle size, polydispersity index, and percentage entrapment efficiency (EE) were the main focuses of optimization. The techniques used for validation included in vitro release tests, in vivo studies, scanning electron microscopy, differential scanning calorimetry, and Fourier transform infrared spectroscopy. Following optimization, 0.591 molar percentage (P: CL) DAS-loaded HPβCD NSPs were created and agitated for 278 min at 3282 rpm, yielding a desirability of 0.706. The selected formulation showed a size of 148.3 ± 2.64 nm, with polydispersity index of 0.221 ± 0.043, with a zeta potential of −22.5 ± 2.83 and EE of 72.62 ± 3.31%%. The effectiveness of the optimization has been verified by a number of analyses, showing significant increases in area under the curve0-t (8.488-times) and Cmax (7.355 times) when compared to the free medication. Conclusion: From this study, we conclude that using NSPs as a delivery system for DAS has great potential for treating advanced tumors by improving release and bioavailability.